Contribution of Arm Explosive Power and Backstroke Flexibility to Plate Serving Ability in Field Tennis Games - Bismar, Ahmad Rum; Hakim, Hikmad; Nawir, Nukhrawi (Sains Global Institut, Indonesia, 2023)
This research aims to determine the contribution of arm explosive power and backstroke flexibility to plate serviceability in field tennis games. This research is a type of quantitative analysis research. The population and sample were tennis athletes from Polewali Mandar district, who were selected using a saturated sample, resulting in a sample of 20 people. The data analysis technique used was frequency using the SPSS Version 21.00 program. Based on the data analysis, it was obtained: 1) there is a significant contribution between the explosive power of the arm and the serviceability of the plate, as proven by the calculated r-value (ro) = 0.501 (p < 0.05). R square 0.251 This means that 25.1% of plate serving ability in tennis is influenced by arm explosive power. 2) There is a significant contribution between the flexibility of the backrest and the serviceability of the plate, as proven by the calculated r-value (ro) = 0.451 (p < 0.05). R square 0.204 This means that 20.4% of the ability to serve the plate in tennis is influenced by the flexibility of the backrest. 3) There is a significant relationship between the explosive power of the arm and the flexibility of the backkick on the serviceability of the plate, as proven by the calculated R value = 0.645 (P<0.05). R square value 0.417. This means that 41.7% of the ability to serve the plate in tennis is explained by the joint variables of arm explosive power and backbend flexibility.